Efektivitas pengomposan sampah organik menggunakan electrical rotary aerobic composter (ERAC) - Iswanto Iswanto; Catur Puspawati; Bambang Suwerda (PUINOVAKESMAS, 2020)
Organic waste that produced in The Polytechnic Health Yogyakarta campus has not been processed and just disposed to Piyungan Landfill. To recycle the organic waste is required engineering technology that can produce compost quickly. Electrical Rotating Aerobic Composter (ERAC) is an aerobic powered electric composter model that is designed to rotate continuously for maintaining the stability of environmental factors (oxygen, temperature, humidity) and the homogeneity of processed organic matter. This study aims to determine effect and effectiveness of rotation speed of the ERAC on duration and quality of compost. This research is an experiment with Post-Test Design Only with Control Group Design. The sample of this research is organic waste that taken by proportionate stratified random sampling in The Polytechnic Health Yogyakarta campus. The composition of organic materials filled in the ERAC consist of 1 part organic waste from the canteen, 1 part of the yard / garden waste, 1 part of cattle manure and 5% active bioactivator. Rotation speed of the ERAC was set with variations: A = 0.20 rpm; B = 0.10 rpm; C = 0.05 rpm; K = 0.00 rpm (control). Each treatment was repeated 3 times and monitored daily until compost was formed. Compost samples are sent and checked for quality in the laboratory. Based on the physical parameters (temperature, color, texture and smell) of compost, showed that ERAC is able to process organic waste into compost within 7 days or four times faster than control (28 days). However, the variation of rotation speed was not significantly affect duration of composting. The quality of compost that produced by ERAC has fulfilled SNI No. 19-7030-2004 including C/N ratio, water content, N, P, K and C-organic. The compost quality according to rotation speed of the ERAC (0,20 rpm; 0,10 rpm; 0, 05 rpm, control (0.00 rpm)) respectively are: C / N ratio (19,83,19,84,19,95,19,90); water content (11,36%; 10,81%; 10,83%; 10,97%); N (1.00%; 1.06%; 1.11%; 1,024%); P (0,57%; 0,60%; 0,58%; 0,64%); K (1.37%; 1.32%; 1.30%; 1.28%); C-organic (19.69%; 20,99%; 21,90%; 20,18%).The result of statistical analysis with Kruskal Wallis test with SPPS program version 16 showed that water content, N, P, C-organic and C / N ratio between the three variations of rotation speed of ERAC is not significantly different, except K level. But when it was associated with workload of the ERAC engine, the lowest rotation speed (0.05 rpm) is the most effective.